Middle manager impacts: Situational leadership on service quality performance - Agni Shanti Mayangsari; Juansih; Wahyu Eko Pujianto (Jurnal Manajemen dan Pemasaran Jasa, 2025)
This study investigates the impact of situational leadership by middle managers on service quality performance in Surabaya's hospitality industry, with Perceived Organizational Support as a moderating variable. Data were collected from 179 valid responses from 15 star-rated hotels, focusing on managerial roles such as Front Office Managers and Executive Housekeepers. A quantitative approach was adopted, employing Structural Equation Modeling (SEM) for data analysis. The results indicate that delegative and supportive leadership significantly enhance service quality, while coaching and directive leadership do not show a significant effect. Moreover, POS significantly improves service quality but does not strengthen the relationship between situational leadership styles and service quality. These findings emphasize the importance of tailoring leadership approaches to specific contexts, highlighting the critical role of delegative leadership and organizational support in fostering service quality. Future research should expand beyond Surabaya and explore other industries to enhance the generalizability of these findings. This study contributes to the contingency theory by examining the dynamic interplay between situational leadership and contextual factors in improving organizational performance.